Podstawowe dyrektywy orzekania w sprawach odpowiedzialności zawodowej lekarzy - Baran-Wesołowska, Beata (PRAWO i WIĘŹ, 2025)
This paper analyzes the scope of application of the principles of the presumption of innocence, the benefit of the doubt, and the free evaluation of evidence by medical tribunals in proceedings concerning medical professional liability. After examining the directives established in Article 61 of the Medical Professions Act, it is concluded that these directives are fundamental principles in cases of medical misconduct. They serve as key guidelines for judicial decision-making, ensuring procedural fairness and rationality.